DEVELOPMENT OF A SEAWEED DRYER USING ARDUINO UNO EQUIPPED WITH AN OLED LCD - Dewi, Sarah; Sidik Sidin, Udin; Tjandi, Yunus; Massikki, Massikki; Muis Mappalotteng, Abdul (Fakultas Teknik Universitas Negeri Makassar, 2024)
This research aims to develop a seaweed dryer using an Arduino Uno equipped with an Oled LCD and to help farmers dry seaweed during the rainy season so that the seaweed is not damaged.This research method uses research and development (R&D) with a prototype development model. The data collection technique used was a questionnaire. The subjects in this research were seaweed farmers in Palajau Village, Arungkeke District, Jeneponto Regency. This research produces a seaweed dryer using an Arduino Uno equipped with an Oled LCD. The result of this research is a prototype seaweed dryer that uses a temperature sensor to detect temperature and humidity, a heater to dry seaweed, a fan to distribute heat in the drying room and an Oled LCD to display temperature and humidity. In terms of Functionality and Usability, the results of the functionality feasibility percentage were 100% and as many as 10 respondents or 100% assessed that the tool developed based on the Usability context was at 100% in the very good category. Based on the results of testing seaweed using this dryer, the drying time for seaweed is 4-5 hours until the seaweed is dry with a capacity of 4 Kg for drying seaweed once.